THE MEANING OF THE PHILOSOPHY WISE (KINAA),BRAVE (BARANI), AND SMART (MANARANG) AS ONE OF THE LOCAL WISDOM OF TORAJA - Tadius Tadius; Benyamin Salu (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
Philosophy is defined as the most basic assumptions, ideas and attitudes possessed by a person or society; views of life; (KBBI online). The local philosophy is more identical to the most basic inner attitudes possessed by a person or society. Along with the development of human civilization, science is increasingly advanced. The advancement of science and technology has had a significant impact on the almost fading of local culture and wisdom in society. The purpose of this research is to deeply analyze the meaning of the philosophy of " wise (kinaa), brave (baran)i, and smart (manarang)" as one of the Torajan local wisdoms that must be passed on from generation to generation. This research was conducted in 3 (three) stages. The first stage is to identify and initial interview the research subjects, namely people who are capable in terms of the Toraja language or those who understand the ins and outs of Toraja culture (Customary leaders). The second stage is to collect data through surveys and further interviews with relevant sources in connection with the three the philosophy of kina, barani and manarang of Toraja local wisdom. The third stage is to manage and analyze data sets and to conduct publications obtained from the results of surveys and interviews regarding the philosophy of kina, barani and manarang in Toraja local wisdom. Based on the results of research and discussion, it is concluded that kinaa contains the meaning of being virtuous, having good character, being helpful, not being selfish. Barani has the meaning of being brave in making decisions, ready to bear the risks of every action taken, daring to say wrong if wrong, and right if right, and having high integrity. Meanwhile, manarang means intelligent, clever, skilled, has broad insight, has a purpose in life, has a visionary spirit.